The unorganised manager (London : Video Arts, 1983)
It tells that there's a big difference between a manager who's busy effectively and one who's merely busy: the difference between doing the job right and doing the right job. This film examines this difference and deals with the central problem of all managers: how best to organise their day and their year to get the best out of themselves and the people who work for them.
backup available in VHS 1/2 in.
Keywords: Time management; Delegation of authority